Cutaneous and systemic improvements in psoriasis patients after different biologic treatments in a real-world longitudinal prospective study - Epipode Ntawuyamara; Baoqing Deng; Yanhua Liang (Scientific Reports)
Abstract Many tools, such as the Psoriasis Area and Severity Index (PASI), are commonly used to evaluate treatment efficacy in clinical settings, but an optimal measure of treatment response may overlook the systemic response in psoriasis patients receiving treatment. This study aimed to assess and compare the co-benefits of adalimumab (ADA), ustekinumab (USTE), ixekizumab (IXE), secukinumab (SECU), and guselkumab (GUSE) during a 24-week follow-up period for the treatment of psoriasis in the Chinese population. We performed a prospective, randomized cohort study including patients receiving systemic biologic treatment for moderate to severe psoriasis. We conducted a follow-up of psoriatic patients treated with five biologics from January 2023 to June 2024 at four time points: baseline, week 4, week 12, and week 24. From baseline through every time point, we used the PASI, BSA (Body Surface Area), DLQI (Dermatology Life Quality Index), and metabolic and inflammatory screening for assessment and comparison of the clinical and systemic efficacy of biologics.This study included 385 participants treated with 5 different biologics. There was a dramatic clinical improvement from baseline to week 24, with a statistically significant difference (p < .001). Overall, 35 patients (9.09%), 145 (37.14%) and 335 (86.75%) achieved PASI 100 at week 4, week 12, and week 24 of the follow-up. Compared with other biologics, IXE (PASI 100 = 12.12% at week 4 vs. 87.27% at week 24) and SECU (PASI 100 = 7.79% at week 4 vs. 89.92% at week 24) were superior. At week 12, a high percentage with PASI 100 was observed for GUSE (38.71%) and SECU (40.28%). ADA and USTE continuously maintained a low percentage of the PASI 100. We observed quicker systemic improvements due to GUSE at time point 2 (p = .041, with low values of total cholesterol (TC) and non-HDL-C, p = .046) and week 24 for TNF-α (p = .024) than other biologics did. SECU and ADA had greater metabolic efficacy for GLU (p = .037 at week 12) and UA (p = .033 at week 24), respectively. This study confirmed the clinical efficacy of biologics and their ability to achieve complete skin clearance and further demonstrated that all biologics can continuously reduce systemic inflammation. We found that biologics have different effects on metabolic dysfunctions, such as SECU on glucose and GUSE on non-HDL.